Development of Science Literacy-Based E-Book Through Differentiated Learning Approach in Science Education - Nurhayati Nurhayati; Tirtawaty Abdjul; Lanto Mohamad Kamil Amali; Sri Wahyuni (Universitas Syiah Kuala, 2026)
The increasing demand for inclusive and student-centered science learning highlights the need for instructional materials that can accommodate diverse student characteristics, learning preferences, and levels of understanding. However, many existing learning resources have not yet optimally supported differentiated learning or effectively fostered students’ science literacy. In response to this gap, this study develops a science literacy-based e-book designed through a differentiated learning approach to expand students' access, participation, and engagement in science learning. The research employs the analysis, design, development, implementation, and evaluation (ADDIE) development model, encompassing five stages: analysis, design, development, implementation, and evaluation. Validation was conducted by three experts assessing content, differentiation, design, and language aspects. The results showed an average score of 4.93 (98.50%), categorized as very valid. Specifically, the differentiation aspect scored 4.83 (96.67%), design and media 5.00 (100%), and language and presentation 4.93 (98.67%), indicating high technical and pedagogical feasibility. Initial student responses (n = 17) yielded an average score of 4.89, while classroom implementation testing (n = 27) showed a 91.5% implementation rate with an average post-learning response of 4.84 and a deviation ≤0.08, reflecting high consistency and satisfaction. These findings indicate that the developed e-book is both valid and practical for supporting differentiated and student-centered science learning. Furthermore, the integration of interactive multimedia elements and differentiation strategies enhances engagement, inclusivity, and science literacy development. This study also provides a foundation for the future development of adaptive digital learning resources